Spatial abilities in male athletes: seasonal variations - Hromatko, Ivana; Tadinac, Meri (2012)
Spatial ability might be considered an integral component of some sports (especially those which require precise visuomotor coordination). It has also been linked with both organizational and activational effects of androgens. While it has been reported that athletes have the increased levels of androgens, there is no clear pattern of results when it comes to differences in spatial ability between athletes and general population. The aim of this study was to a) explore the differences between athlete and non-athlete students in two different types of spatial abilities - mental rotations and spatial visualization ; and b) test for seasonal variations in those two types of spatial ability (in relation to activational effects of testosterone, which is higher in autumn than in spring). A total of 170 athlete and 125 non athlete male students participated in the study. The results showed that athletes did outperform non-athletes in mental rotations, but not in spatial visualizations. Likewise, there was a significant seasonal effect in ability to mentally rotate, but not in the ability to visualize space. Athletes tested in autumn had significantly lower scores in mental rotation than athletes tested in spring, which is in accordance with the proposed curvilinear relationship between testosterone and spatial ability. Previously reported inconsistencies in comparison between athletes and general population might be due to the non-unitary nature of spatial abilities: thus athletes might excel in mental rotations, but not in the other forms of spatial ability.
Projekt MZOS
ENG